(untitled) (Bangladesh Journal of Medical Science, 2018)
Introduction: Hysterectomy is the most commonly performed gynaecological surgery in India as well as in abroad. It is frequently done in myometrial and endometrial pathologies and rarely for other causes. Hysterectomy is definitive management for diseases like fibroid, adenomyosis, dysfunctional bleeding, prolapsed uterus and malignant lesions of uterus and adenexa. We aimed our study to observe incidence of different pathologies of uterus and other reproductive organs in hysterectomy specimens and retrospective correlation between clinical diagnosis and histopathological finding of hysterectomy cases. Materials and Methods: Retrospective data were collected from our routine histopathological laboratory. Detailed history, clinical examination and operative findings and provisional diagnosis of all 950 hysterectomy cases were recorded during study period of 2 years. Histopathological diagnosis was correlated with clinical and preoperative diagnosis. Observations: Abdominal hysterectomy (734 cases, 77.26%) was the most common route of approach during surgery. Common pre-operative diagnoses were fibroid uterus (32%), dysfunctional uterine bleeding (28.95%), uterine prolapsed (22.74%). Other causes included uterine polyps (1.6%), complications of pregnancy (2.74%), ovarian tumours (8.42%), cervical carcinomas (2.97%) etc. Common pathologies on histology were leiomyoma (32%), adenomyosis (20.32%), atrophic endometrium (17.26%) and endometrial pathology (8.95%). Discussion: Our study has been correlated with other studies of India and other south Asian countries. Most common indication of hysterectomy in our study is dysfunctional uterine bleeding (32%) but Gupta et al and Jha R et al found utero-vaginal prolapse as most common indication. Leiomyoma was the most common histology diagnosed in the present series. Clinical diagnosis was possible in 67.57% cases in our study similar to Khan et al (70.51%). Conclusions: Histopathological examination of hysterectomy specimens helps to detect the exact causes and underlined pathology. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.88-92